The small GTPase NtRHO1 negatively regulates tobacco defense response to tobacco mosaic virus by interacting with NtWRKY50. (6th September 2021) - Han, Hongyan; Zou, Jialing; Zhou, Jingya; Zeng, Mengyuan; Zheng, Dongchao; Yuan, Xuefeng; Xi, Dehui
Abstract : The novel small GTPase NtRHO1 negatively regulates tobacco resistance to tobacco mosaic virus by interacting with transcription factor NtWRKY50, resulting in the suppression of immunity-related genes. Abstract: Small GTPases play critical roles in the regulation of plant growth and development. However, the mechanism of action of small GTPases in plant response to virus infection remains largely unknown. Here, the gene encoding a Rho-type GTPase, NtRHO1, was identified as one of the genes up-regulated after tobacco mosaic virus (TMV) infection. Subcellular localization of NtRHO1 showed that it was located in the cytoplasm, plasma membrane, and nucleus. Transient overexpression of NtRHO1 in Nicotiana benthamiana accelerated TMV reproduction and led to the production of reactive oxygen species. By contrast, silencing of NtRHO1 reduced the sensitivity of N. benthamiana to TMV-GFP. Further exploration revealed a direct interaction between NtRHO1 and NtWRKY50, a positive regulator of the N. benthamiana response to virus infection. Yeast one-hybrid and electrophoretic mobility shift assays showed that this regulation was related to the capacity of NtWRKY50 to bind to the WK-box of the PR1 promoter, which was weakened by the interaction between NtRHO1 and NtWRKY50. Thus, our results indicate that the small GTPase NtRHO1 plays a negative role in tobacco response to TMV infection by interacting with transcription factor NtWRKY50, resulting in reduced plant immunity.